The Role and Management of School Public Health - Sukatin, Sukatin; Asvio, Nova; Sari, Oci Mulia (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of the research was to identify an explanation of the role and management of School Public Health (UKS) in Madrasah Ibtidaiyah Negeri (MIN) 2 Bengkulu City. This research uses descriptive qualitative research principles. Data were collected through observation, question and answer methods, and archiving studies. The review method is collected through the process of reducing data, presenting data, and drawing final results. Based on research, it was revealed that the UKS conditions in the MIN 2 environment were classified as good, especially before the UKS pandemic played a very important role because every sick child or the surrounding community and teachers at MIN 2 immediately received help or received assistance if they were sick or had other complaints. However, in government policy based on the Covid-19 condition, the UKS management was stopped based on the results of interviews from the Principal, Teacher Staff, UKS Main Manager and Students and Students at MIN 2.